2013
DOI: 10.1007/s40262-013-0105-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pharmacokinetics of Clopidogrel and Its Metabolites in Patients with Cardiovascular Diseases

Abstract: Background and ObjectiveApproximately 5–40 % of patients treated with clopidogrel do not display an adequate antiplatelet response. Clopidogrel resistance may be caused by insufficient drug absorption or impaired metabolic activation of the drug. The aim of this study was to evaluate the pharmacokinetics of clopidogrel and its metabolites in plasma samples from patients treated with high and low doses of clopidogrel, to obtain a possible explanation for antiplatelet resistance.MethodsThe study included patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
61
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 37 publications
2
61
1
Order By: Relevance
“…Because of the different catalytic efficiencies of the P450 isoforms and TMT in the formation and S-methylation of H3 and H4, determining the exposure and pharmacokinetic parameters for H4 indirectly by quantifying H3 or the mixture of H3 and H4 would be unsuitable for evaluating the pharmacokinetics and pharmacodynamics relationship. This hypothesis was proven in a clinical study in which C max of H4 rather than H3 was correlated with platelet aggregation in humans after oral administration of clopidogrel (Kara zniewicz-Łada et al, 2014). More studies are required to investigate the role of the epimerization of thiolactone 2 and TMT in the variability in response to clopidogrel therapy.…”
Section: Discussionmentioning
confidence: 96%
“…Because of the different catalytic efficiencies of the P450 isoforms and TMT in the formation and S-methylation of H3 and H4, determining the exposure and pharmacokinetic parameters for H4 indirectly by quantifying H3 or the mixture of H3 and H4 would be unsuitable for evaluating the pharmacokinetics and pharmacodynamics relationship. This hypothesis was proven in a clinical study in which C max of H4 rather than H3 was correlated with platelet aggregation in humans after oral administration of clopidogrel (Kara zniewicz-Łada et al, 2014). More studies are required to investigate the role of the epimerization of thiolactone 2 and TMT in the variability in response to clopidogrel therapy.…”
Section: Discussionmentioning
confidence: 96%
“…Whether ABCB1 C3435T polymorphism influences the concentration of clopidogrel metabolites is still inconclusive. Some studies show the association only at the prodrug level [24] . Mega et al [25] suggested that it did not affect maximum plasma concentration of thiol clopidogrel metabolite achieved.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction of the collected blood samples can be useful from the clinical and also economical point of view. Strategies using a limited number of samples are useful also in therapeutic monitoring of anticoagulant drugs [20] and immunosuppressants [21].…”
Section: Discussionmentioning
confidence: 99%